The Confident Writer: A Norton Handbook - Gefvert, Constance J. (New York W.W. Norton and Company, 1985)
Both reference handbook and writing textbook, The Confident Writer: A Norton Handbook is designed to give students the help they need to write with confidence in any writing situation, in college and beyond. From the beginnings of the writing process through the final editing stages, this handbook will help students make choices of thesis, suporting arguments and details, paragraph and sentence structure, and words that will allow them to write with persuasive power.
Keywords: Writing